2015
DOI: 10.1111/1756-185x.12618
|View full text |Cite
|
Sign up to set email alerts
|

Elevated autoantibodies against interleukin‐17F correlate with disease activity in patients with early rheumatoid arthritis

Abstract: Elevated aAbs against IL-17F correlate with disease activity in patients with ERA. This evidence suggests that anti-IL-17F aAbs may have a protective role in the pathogenesis of ERA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Their findings indicated that antibody increase in response to IL-17 was directly related to the disease activity of those patients. Such evidence suggests that antibodies against IL-17 may play a protective role against the pathogens of such diseases (Yang et al, 2015). Liu et al, studied the role of IL-17 levels in the synovial fluid and its relationship with knee-arthritis intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicated that antibody increase in response to IL-17 was directly related to the disease activity of those patients. Such evidence suggests that antibodies against IL-17 may play a protective role against the pathogens of such diseases (Yang et al, 2015). Liu et al, studied the role of IL-17 levels in the synovial fluid and its relationship with knee-arthritis intensity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, anti-TNF-α and anti-IL-17 autoantibodies were detected in RA patients. In addition, anti-IL-17A antibodies were associated with bone destruction and disease activity [9][10][11]. The generation of ACAAs was due to the loss of B cell tolerance caused by the overexpression of key inflammatory cytokines and chemokines [12].…”
Section: Introductionmentioning
confidence: 99%